2018
DOI: 10.1177/1609406918794255
|View full text |Cite
|
Sign up to set email alerts
|

Using Solicited Written Qualitative Diaries to Develop Conceptual Understandings of Sleep

Abstract: This article presents the use of the solicited written qualitative sleep diary as a method for understanding sleep experience. The article reviews selected quantitative and qualitative research to contextualize contemporary sleep circumstances and concerns. It continues with a summary of previous diary applications in social scientific sleep research. The article then outlines the diary template, data collection procedures, and sampling. Diaries were received from a sample of 48 university students at a Canadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Processes were in place to support both the researchers and the diarists in the event of emotional distress, with weekly calls used to check in with diarists. All quotes and excerpts in the findings are anonymized using an identifier combining the diarist's unique ID (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and the diary week (1)(2)(3)(4)(5)(6)(7)(8). Where data come from weekly calls, this is stated (e.g., diary5-week1-call).…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Processes were in place to support both the researchers and the diarists in the event of emotional distress, with weekly calls used to check in with diarists. All quotes and excerpts in the findings are anonymized using an identifier combining the diarist's unique ID (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and the diary week (1)(2)(3)(4)(5)(6)(7)(8). Where data come from weekly calls, this is stated (e.g., diary5-week1-call).…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…The solicited diary method, designed for research purposes (as opposed to private diary keeping), is recognized to have advantages 11 . Temporally, they allow for the recording of changing experiences (e.g., over days, weeks or months) 12 . For some, diary writing may lead participants to reveal more private insights into situations that they are less willing to discuss in an interview context 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, regular contact with participants have been found to enhance the quality and rigor of the diaries produced (Herron et al, 2019). Indeed, research has shown that participants may request assurance from researchers that they are completing the diary research task in a proper way (Gawley, 2018). For instance, Moore et al (2015) noted that the home visits during the writing of diaries by older people on the self-management practices of heart disease enabled researchers to build rapport.…”
Section: Powermentioning
confidence: 99%
“…Diaries also open space for the creative expression of participants (Alaszewski, 2006). Indeed, Gawley (2018) in a study on the sleep experience of university students noted that creativity and complexity of thought marked the writing of diaries.…”
Section: Powermentioning
confidence: 99%